Semantic Space of Character’s Smile in Sholokhov’s Novel “The Quiet Don” (Proceedings of Southern Federal University. Philology, 2021)
Nina А. Dvoryashina (Surgut, Russian Federation)The article is devoted to the study of the role of a smile in creating images of the characters of the novel of М. А. Sholokhov “The Quiet Don”, disclosing their psychological state. The study revealed that one of the important and distinctive techniques in characterizing this non-verbal gesture is its metaphorical description. Its analysis allowed the author of the article to come to the following results: 1) most often Sholokhov uses such varieties of this means of expressiveness as metaphors of light, temperature, movements reflecting not only the mental experiences of the characters, but also essential features of their characters; 2) words similar in semantics in the characteristic of a smile are distinguished by a variety of meanings in the transmission of feelings experienced by characters; 3) writer’s style is dominated by the dynamic form of transmitting this portrait detail: smile affects others, lives an «independent» life, physically changes the appearance of its carrier, obeys his strong-willed decisions; 4) it is not only a means of expressing a person’s psychological state, but a way of reflecting the interaction of its inner world with the surrounding reality; 5) this mimic gesture is distinguished by Sholokhov’s special emotional expressiveness, figurative identity. The results of the study are important for understanding the writer’s innovation in artistic knowledge of a person’s identity, an in-depth understanding of his creative individuality.Key words: Sholokhov, «The Quiet Don», character, mimic gesture, smile, metaphor, emotion, semantics.DOI 10.18522/1995-0640-2021-2-39-53